Aquisição da segunda língua em contexto de escola bilíngue: uma pesquisa teórica a partir da teoria histórico-cultural - Venanzi, Rafaela (Universidade Federal de São Carlos, 2025)
This research aimed to understand the process of second language acquisition in bilingual school contexts from the perspective of Historical-Cultural Theory. Through a systematic literature review and an articulated analysis of authors such as Vygotsky, Pasqualini, Martins, Lantolf, García, Wei, and other scholars of bilingualism and translanguaging, it was possible to ascertain that L2 acquisition constitutes an eminently social, mediated, and culturally situated phenomenon, distancing itself from nativist and mechanistic perspectives frequently associated with language learning.
Second language acquisition in a bilingual school context: a theoretical study based on historical-cultural theory
Keywords: Bilinguismo; Teoria histórico-cultural; Práticas pedagógicas; bilingualism; historical-cultural theory; pedagogical practices; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade